Audio-visual aids for livestock extension programmes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Information transfer cannot be limited to the printed word: audio-visual techniques are also an important tool, especially for extension workers involved primarily with illiterate farmers. CTA has therefore decided to participate in a video...